2003
DOI: 10.4081/ijas.2003.29
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactation stage, parity, β-lactoglobulin genotype and milk SCC on whey protein composition in Sarda dairy ewes

Abstract: In 90 Sarda dairy ewes the effects of lactation stage, parity, β-lactoglobulin genotypes, and somatic cell count (SCC) on the milk content of total protein (TP), casein (CN), whey protein (WP) and its fractions α-lactalbumin (ALA), β-lactoglobulin (BLG), serum albumin (SA), immunoglobulin (IG) and lactoferrin (LF) were analysed using a linear mixed model. Mean values of variables (g/l) were: TP (54.0), CN (43.0), WP (11.0), BLG (4.78), ALA (1.37), SA (0.61), IG (3.83) and LF (0.28). The lactation stage signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
1
14

Year Published

2007
2007
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 23 publications
8
35
1
14
Order By: Relevance
“…A significant increase (P<0.0001) in β-lactoglobulin concentration was observed in infected glands compared to that in healthy ones (Table 1, Fig.4), which is in agreement with the results of Nudda et al (2003), who observed significant increases in β-lactoglobulin in the whey of sheep with mastitis with somatic cell counts higher than 1.000.000. These results differ from that reported in other studies involving ruminants.…”
Section: Discussion Total Proteinsupporting
confidence: 81%
See 3 more Smart Citations
“…A significant increase (P<0.0001) in β-lactoglobulin concentration was observed in infected glands compared to that in healthy ones (Table 1, Fig.4), which is in agreement with the results of Nudda et al (2003), who observed significant increases in β-lactoglobulin in the whey of sheep with mastitis with somatic cell counts higher than 1.000.000. These results differ from that reported in other studies involving ruminants.…”
Section: Discussion Total Proteinsupporting
confidence: 81%
“…Similar results have been reported by Nudda et al (2003), who observed a two-fold increase in lactoferrin concentrations in whey samples from sheep with somatic cell counts above one million. Sant'ana (2004) also reported a two-fold increase in lactoferrin concentration in cows with mastitis, and Raimondo et al (2011) reported a significant increase in lactoferrin concentration in goats with mastitis, highlighting the precociousness of its appearance compared to that of other whey proteins.…”
Section: Discussion Total Proteinsupporting
confidence: 79%
See 2 more Smart Citations
“…Numerous authors have shown that a high level of somatic cells in ewe milk is connected with a higher protein percentage compared with the protein content in low SCC milk (Nudda et al, 2003;Albenzio et al, 2004;Bianchi et al, 2004). However, other authors reported low protein contents in milk with a high SCC (Jaeggi et al, 2003).…”
Section: Introductionmentioning
confidence: 84%